DASAR SPIRITUAL MANAJEMEN KONFLIK GEREJA MULA-MULA: MENURUT KITAB KISAH PARA RASUL - Dihamri; Iwan Setiawan; Nurmintan Silaban; Sujsan Silvia Moningka (Manna Rafflesia, 2023)
Conflict management is a method used to guide interactions within a social group, both between individuals and groups, to create harmony. In this context, it deals with conflict management within the church to create harmony and peace. But the fact is that many churches today are experiencing internal and external conflicts, not a few of which eventually the church has split, and many church denominations have broken up because they cannot resolve a conflict. The church does not have a reasonable basis for conflict management, so problem-solving tends to follow logic rather than the leading of the Holy Spirit or spiritual things. The purpose of this study is to explain the essential conflict management of the early church based on the Acts of the Apostles so that it can be a reference for today's church in resolving conflicts that occur within the church. The method used is a qualitative approach with an analytical description method, describing it in a hermeneutic way, namely by interpreting several verses in the story of the apostles, which then become the basis for conflict management. Researchers obtained research results: First, the Early Church Lived in Repentance. Second, the Early Church Lived in the Teachings of the Apostles or the Word of God. Third, the early church lived in prayer and close communion. Fourth, the Early Church Established Good Communication. Fifth, the Early Church Did Not Live in Selfishness.